CSR Implementation Program of PT. IMIP on Economic Empowerment and Environmental Sustainability of The Surrounding Community - Masyam, Naufal Alfaruqi; Mahyuni, Enni Tri; Samanlangi, Andi Ilham; Noor, Moh. Khaidir; Ma'rief, A. Al Faizah; Hedianto, H.; Taliding, Tri Utomo; Munandar, Aris (Manunggal Halim Jaya, 2025)
As one of the largest mining companies, PT. IMIP is a nickel processing industrial area. Therefore, a Corporate Social Responsibility is needed, which is a form of corporate responsibility towards the community around the company's operational location. The research method employs a qualitative approach, utilizing literature studies as the primary source for writing scientific papers, by collecting data from various valid and reliable reference sources. The results of the study show that PT. IMIP, in carrying out its own CSR, is a company that looks at the Triple Bottom Line concept, also known as 3P (Profit, People & Planet). In generating good profits, PT Indonesia Morowali Industrial Park not only focuses on achieving financial gains, but is also committed to improving the economic welfare of the community, protecting the environment, and, of course, benefiting the environment and its surroundings. It can be seen from the allocation of CSR funds of IDR 170 billion over the past three years, which have been distributed to support the economic sector of the surrounding community. This demonstrates that the implementation of CSR at PT. IMIP can be considered successful.